The Sufian Symbol and its significance in Abd Allah Hamadi's Poetry (Journal of the College of Education for Women, 2019)
This research paper looks to put its hands on sufi symbols which are applied by the algerian poet د abdallah hammadi د in his poetical works . the symbols it relies on are : ( symbolisme of wine . symbolisme of light . symbolisme of night . sufisme and nature , femal symbols ) .From these symbols we try to show its range of ability to apply it , with trying to determine its meaningful , dimensions .